Validation in mesenchymal progenitor cells of a mutation-independent ex vivo approach to gene therapy for osteogenesis imperfecta - Humphries, Peter; Farrar, Gwyneth (My University, 2002)
Over 100 dominant-negative mutations within the COL1A1 gene have been identified in osteogenesis imperfecta (OI). In terms of human therapeutics, targeting each of these mutations independently is unlikely to be feasible. Here we show that the hammerhead ribozyme Rzpol1a1, targeting a common polymorphism within transcripts from the COL1A1 gene, downregulates COL1A1 transcript in human mesenchymal progenitor cells at a ribozyme to transcript ratio of only 1:1. Downregulation was confirmed at the protein level. Transducing stem cells with Rzpol1A1 ex vivo followed by autologous transplantation could provide a gene therapy for a large proportion of OI patients with gain-of-function mutations using a single therapeutic.
PUBLISHED
Keywords: Molecular biology; Human genetics